ChemInform Abstract: Efficient, Diversity, and Complexity with Multicomponent Reactions. Issue 23 (16th May 2013) - van der Hejjden, Gydo; Ruijter, Eelco; Orru, Romano V. A.
Abstract Review: about 100 refs.